APPLICATION OF BASIC ACCOUNTING CONCEPTS WITH TRAINING METHODS FOR PREPARATION OF FINANCIAL STATEMENTS FOR BUSINESSES (International Journal of Innovative Technologies in Economy, 2024)
Micro, Small and Medium Enterprises (MSMEs) are the driving wheels of the economic cycle, because SMEs are able to absorb a large workforce. They are one form of business that can survive and contribute to large growth in gross domestic product. The accounting cycle is the process of each accounting which is carried out by searching for analysis, recording using processes which are carried out repeatedly and analyzing existing records. SAK EMKM is very helpful for SME owners in implementing accounting in their businesses to make it easier to prepare finances according to standards. Based on SAK EMKM, SME actors are required to make proper reports, namely by keeping daily, weekly, monthly and annual financial records because financial reports are very important for the progress of a business. If we relate it to our hypothesis, SAK EMKM has not been carried out in Cireundeu, considering that Cireundeu SMEs only make Income and Expenditure reports. In particular, the implementation of accounting for SMEs in Cireundeu Village still has the same problems as several regions in Indonesia, so solutions and approaches to increasing SME accountability must be prepared by a user-friendly and systematic accounting process guide based on EMKM by SME managers.